2004
DOI: 10.2135/cropsci2004.5750
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Perennial Ryegrass for Resistance to Gray Leaf Spot

Abstract: genic races; thus, host resistance genes remain effective for only a few years before the pathogen population Gray leaf spot, caused by the fungus Pyricularia grisea (Cooke) shifts to new virulent races (Bonman et al., 1992; Zhu Sacc. [teleomorph Magnaporthe grisea (T.T. Herbert) Yaegashi & Udagawa], can be a devastating disease on perennial ryegrass (Lolium et al. , 2000). This has led researchers to identify durable perenne L.). The identification and utilization of perennial ryegrass (quantitative) resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 18 publications
3
18
1
Order By: Relevance
“…This study agrees with the former study (Bonos et al, 2004) in that resistance could be rapidly improved through a genotypic recurrent selection program. However, additive gene effects were the major factor in gray leaf spot resistance evaluated in these perennial ryegrass plants.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study agrees with the former study (Bonos et al, 2004) in that resistance could be rapidly improved through a genotypic recurrent selection program. However, additive gene effects were the major factor in gray leaf spot resistance evaluated in these perennial ryegrass plants.…”
Section: Discussionsupporting
confidence: 92%
“…Bonos et al (2004) reported that a major gene for gray leaf spot resistance was segregating in the resistant perennial ryegrass populations. Assumedly, there could be more than three to five genes involved in gray leaf spot resistance in these crosses.…”
Section: Number Of Genesmentioning
confidence: 99%
“…By incorporating native germplasm into naturalized populations, genetic diversity increases, which can result in the development of cultivars with improved traits or increased fitness. One example of this is the development of gray leaf spot (caused by Pyricularia oryzae) disease resistance in perennial ryegrass cultivars (Bonos et al, 2004). When the disease was first reported in North America, no commercial cultivars were found with gray leaf spot resistance.…”
Section: Bluegrass Speciesmentioning
confidence: 99%
“…When the disease was first reported in North America, no commercial cultivars were found with gray leaf spot resistance. After an epidemic of gray leaf spot in 2000, ~13% of the Rutgers perennial ryegrass germplasm contained some level of gray leaf spot resistance (Bonos et al, 2004). Approximately 50% of the resistant germplasm traced to plants collected from North America and 50% traced to European collections that had been backcrossed with North American germplasm.…”
Section: Bluegrass Speciesmentioning
confidence: 99%
“…Unfortunately, under the current situation, this approach does not promise to be all that useful for managing gray leaf spot because most prg germplasm is susceptible to the disease (Hofmann and Hamblin, 2000; Vaiciunas and Clarke, 1998). Nevertheless, a small number of cultivars with improved levels of resistance have been recently developed and released for public use (Bonos et al ., 2004; Cai et al ., 1997; Samudio and Brede, 2004). In these cases, resistance functions by reducing disease severity and, as such, is quantitative in nature.…”
Section: Introductionmentioning
confidence: 99%